The validity of learning tools based on guided inquiry learning on the topic of respiratory system - Halid, Rizka; Lamondo, Djuna; Yusuf, Frida Maryati; Husain, Ilyas; Latjompoh, Masra; Solang, Margaretha (Journal of Research in Instructional, 2023)
This research aims to analyze the validity of learning tools based on guided inquiry learning on respiratory system material. Research and development of the ADDIE model were used in this research. This research was limited to the "develop" stage, which was limited to the results of expert validation tests. The learning tools developed include lesson plans (four meetings), student worksheets (four meetings), and tests (a total of six items in the form of essays). Two experts and one practitioner validated the learning tool—analysis by calculating the acquisition score based on the validator's assessment. The findings reveal that the lesson plans, student worksheets, and tests have been proven valid according to validity standards. This research concludes that inquiry-based learning tools are valid based on expert assessment. Thus, learning tools based on guided inquiry are suitable for biology learning in high school, especially material on the respiratory system.